Production Techniques of Mosaics in Pamphylia, Cilicia and Northern Syria from the Hellenistic Period to the end of the IVth Century A.D. - Yağmur TOPALOĞLU (Phaselis: Disiplinlerarası Akdeniz Araştırmaları Dergisi)
Mosaics were used for both visual and functional purposes in ancient times, whereas today they are mainly used for their visual impact. Mosaic tiles gives important information about the period they belong to. In addition to the history and art of the period, they also provide information about the aesthetic taste, status, education level of the person who made the flooring. In ancient sources, it is mentioned that mosaics are actually a status symbol. Beside this, there is information about the production process and techniques of mosaics. This article presents a comprehensive evaluation of floor coverings in Pamphylia, Cilicia and Northern Syria from the Hellenistic Period to the end of the IVth century AD. It builds on previous research and offers new insights. By emphasizing various points, the floors of each region were first examined within its own region. This study has revealed a number of key findings regarding the development of mosaic art in the coastline formed by the aforementioned regions. It has also identified the interaction of the mosaics in these regions and the impact this interaction has had on the floors. In addition, it has examined the influence of mosaic workshops and pattern catalogues on the floors, as well as the mosaic production techniques, architectural contexts in which the floors are located and the materials used in the floors.